2022
DOI: 10.1111/ijcs.12835
|View full text |Cite
|
Sign up to set email alerts
|

Effects of shared characteristics between eco‐labels: A case for organic and local food

Abstract: Food labels are created to reduce information asymmetry and help consumers make better food choices. However, the labels may have unanticipated effects, especially when they share common characteristics that may introduce confusion in making food choices. This study investigates how perceived relationships between different food labels may affect the price premiums of organic and local attributes for milk and fresh strawberries. Results show that the impacts of perception vary by product and label, and differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 75 publications
0
5
0
2
Order By: Relevance
“…Certain facets of CBFLE have also been examined in the literature, most commonly consumers' awareness, understanding, and trust (Chen et al, 2015;Feucht & Zander, 2014;Grunert et al, 2014). Furthermore, Sigurdsson et al (2022) examined how familiarity with a food label mediates the effect of the label on WTP, and Donato and Adigüzel (2022) studied how label design affects consumers' evaluations of sustainable products.…”
Section: Consumer-based Food Label Equity (Cbfle)mentioning
confidence: 99%
“…Certain facets of CBFLE have also been examined in the literature, most commonly consumers' awareness, understanding, and trust (Chen et al, 2015;Feucht & Zander, 2014;Grunert et al, 2014). Furthermore, Sigurdsson et al (2022) examined how familiarity with a food label mediates the effect of the label on WTP, and Donato and Adigüzel (2022) studied how label design affects consumers' evaluations of sustainable products.…”
Section: Consumer-based Food Label Equity (Cbfle)mentioning
confidence: 99%
“…Despite the debates on the validity of using this method, a meta‐analysis of different practices of eliciting consumers' MWTP finds that direct measurement methods such as CVM are less likely to overestimate consumers' MWTP than other indirect measurements, such as choice experiments (Schmidt & Bijmolt, 2020). The payment card method is one of the prevalent CVMs to evaluate consumers' MWTP in the literature (Chen et al, 2023; Yang et al, 2013; Yu et al, 2014). The payment card method asks respondents to choose a number or an interval from a list of given values.…”
Section: Data Collectionmentioning
confidence: 99%
“…However, general awareness of eco‐labels is not quite adequate to drive eco‐label uptake, instead past research has shown that specific awareness, which includes the ability to recognize and recall labels and understand their benefits (Henninger, 2015; Taufique et al, 2019; Thøgersen, 2000) is crucial for consumers to adopt them. In terms of food eco‐labels, while they do follow specific regulations and serve specific purposes, they often share common characteristics and communicate complex multifaced information (Chen et al, 2022). For example, organic, local, and green food labels all signify pro‐environmental practices in the production process, which is a shared overarching characteristic, however, local food also showcases carbon miles, whilst organic food labels certify no use of chemicals or genetic techniques in farming, and green food labels signify no use of toxic and environmental pollutants during the production process (Moruzzo et al, 2020; Eco‐label Index, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The complex information is hard to process easily by the consumers who are using eco-labels as clues and signals of trust to reduce the information search and information processing time while making purchase decisions. Thus, overlapping characteristics and a lack of clarity and multiplicity of information may cause ambiguity and misunderstanding among consumers about what eco-labels' signal and what their benefits are (Hu et al, 2012;Syrengelas et al, 2018) and thus, lead to ineffective and inefficient use by consumers (Chen et al, 2022). This could imply that consumers may single out one characteristic or benefit they associate with eco-labels in general when making a purchase decision, rather than reflecting on all and/or specific characteristics of individual labels.…”
mentioning
confidence: 99%